Isolation and characterization of a β-galactosidase from a new Amazon forest strain of Aspergillus niger as a potential accessory enzyme for biomass conversion - Tonelotto, Mariana; Pirota, Rosangela Donizete Perpetua Buzon; Delabona, Priscila Da Silva; Barros, Georgia De Oliveira Figueiredo; Golubev, Alexander M.; Polikarpov, Igor; Farinas, Cristiane Sanchez (Taylor & Francis, 2014)
The selection of enzyme-producing fungi is useful to obtain enzymes required to hydrolyze lignocellulosic material and thereby contribute to biomass conversion into fuels and chemicals. Besides cellulases, the presence of accessory enzymes in enzyme cocktails is necessary to enhance hydrolysis efficiency. This study evaluates the production, purification, and biochemical-kinetic characterization of β-galactosidase produced by a new strain of Aspergillus niger (P47C3) isolated from the Amazon Forest. The A. niger (P47C3) was cultured under SmF conditions and β-galactosidase was purified in a three-step purification, using an ultrafiltration membrane, ion exchange (TSK-SP), and gel filtration (Sephacryl S-200). The calculated molecular weight of the purified enzyme was 125 kDa. Optimum pH (4.0) and temperature (55°C) of β-galactosidase activity were determined. The values of the kinetic parameters obtained from p-nitrophenyl-β-D- galactopyranoside (PNPG) hydrolysis were 2.2 mM and 0.285 mM/min for Km and Vmax, respectively. The inhibition of PNPG hydrolysis by β-galactosidase in the presence of the inhibitor galactose gave a Ki value of 5.01 mM. As a precursor to elucidating the tertiary structure using X-ray diffraction, the β-galactosidase was crystallized using 0.2 M Tris-HCl buffer, with 12% PEG 4000 as the precipitation agent; the largest crystals were formed at pH 8.6. These results provide the basis for further structural and functional studies of this accessory enzyme to evaluate its potential biotechnological applications. © 2014 Informa UK, Ltd.
Keywords: Accessory enzymes; Amazon; Aspergillus niger; Biomass; β-galactosidase